The study of religious traditions: approaches and theories - Hashi, Abdurezak Abdulahi (IIUM Press, 2014)
This book, The Study of Religious Traditions, addresses number of issues and themes of the study of religious traditions. It elucidates basic concepts of comparative religion, and highlights issues of subjectivity and objectivity, as well as the history, approaches, theories and methodologies of this field. In addition, it presents a descriptive account on the Islamic understanding of religious traditions; it illustrates the basic concepts and categories of religious traditions through and within the Qur’anic verses. Likewise, an exposition of the unity of God among Abrahamic traditions is sought, while the debates of the modern socio-anthropological theories about the history and the origin of religion are presented in this book.